Pengaruh Kecerdasan Emosional dan Quality of Work Life Terhadap Kinerja Perawat - Astria Utami Sri Reski; Almansyah Rundu Wonua; Ismanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine: (1) The Effect of Emotional Intelligence on Nurse Performance (Study at Antam Pomalaa Hospital). (2) The Effect of Quality of Work Life on Nurse Performance (Study at Antam Pomalaa Hospital). This research uses a quantitative method approach. Data collection in this study used observation, documentation and questionnaires. The population of this study were all nurses at Antam Pomalaa Hospital. While the sample of this study amounted to 34 nurses by determining the sample using the census technique. Testing of research instruments using validity tests and reliability tests with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 3.0. Based on the results of the study, it is known that the Emotional Intelligence variable has a positive and significant effect on Nurse Performance as indicated by the P-Values value of 0.039. And the Quality of Work Life variable also has a positive and significant effect on Nurse Performance, this is indicated by the P-Values value of 0.017.